SDG-Integrated Social Studies Instruction and Global Citizenship Competence Among Grade 5 Learners in Cabuyao City: Basis for Instructional Framework - Jacqueline B. Empang; Randy D. Punzalan (Edu Berkah Khatulistiwa, 2026)
This study examined the integration of Sustainable Development Goal (SDG) 4.7 in Social Studies (Araling Panlipunan) instruction and its relationship to the global citizenship competence of Grade 5 learners in Cabuyao City. Anchored on the UNESCO Global Citizenship Education framework and Social Constructivism, the study aimed to determine the extent of SDG 4.7 integration in terms of pedagogical approaches, instructional resources, curriculum localization, and contextualized assessment, and to assess learners’ global citizenship competence across cognitive, socio-emotional, and behavioral domains. An explanatory sequential mixed-methods design was employed. Quantitative data were collected from 294 Grade 5 learners using a validated survey instrument and analyzed using weighted mean and Spearman’s rho. Qualitative data were collected from all Grade 5 Social Studies (Araling Panlipunan) teachers (n = 7), representing 100% of the target teacher population in the selected schools, through semi-structured interviews and analyzed using thematic analysis to explain and enrich the quantitative findings. Results revealed that SDG 4.7 was integrated at a very high level across all instructional components, while learners demonstrated a high level of global citizenship competence. A significant positive relationship was found between SDG 4.7 integration and global citizenship competence, with low to moderate positive correlations (ρ= 0.469–0.592, p < 0.05). Qualitative findings identified challenges such as limited resources and time constraints, as well as effective practices including contextualization, experiential learning, and real-life application strategies. The study concludes that SDG 4.7–integrated instruction effectively supports learners’ knowledge and values formation; however, sustained behavioral engagement requires continuous, context-based, and action-oriented learning experiences. These findings informed the development of an instructional framework to enhance Social Studies instruction and strengthen global citizenship competence.